2016
DOI: 10.1038/pr.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Microarray gene expression analysis in ovine ductus arteriosus during fetal development and birth transition

Abstract: BACKGROUND Patent ductus arteriosus (PDA) in the newborn is the most common congenital heart anomaly and is significantly more common in preterm infants. Contemporary pharmacological treatment is effective in only 70–80% of the cases. Moreover, indomethacin or ibuprofen, which are used to close a PDA may be accompanied by serious side effects in premature infants. To explore the novel molecular pathways, which may be involved in the maturation and closure of the ductus arteriosus (DA), we used fetal and neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Otherwise, our past work (3) aligns itself with that of Goyal et al (1) in highlighting the role of certain genes in promoting the maturation of the ductus. In particular, we may add support to the proposed involvement of the Wnt-planar cell polarity/Wnt-β-catenin pathways by showing not only the presence of genes coincident with the listing of Goyal et al (1), but also the likely contribution of a separate cohort of functionally allied genes ( Table 1).…”
supporting
confidence: 75%
See 3 more Smart Citations
“…Otherwise, our past work (3) aligns itself with that of Goyal et al (1) in highlighting the role of certain genes in promoting the maturation of the ductus. In particular, we may add support to the proposed involvement of the Wnt-planar cell polarity/Wnt-β-catenin pathways by showing not only the presence of genes coincident with the listing of Goyal et al (1), but also the likely contribution of a separate cohort of functionally allied genes ( Table 1).…”
supporting
confidence: 75%
“…Cadherin 1 Data from our study (3), with entries in bold being common to the study of Goyal et al (1). Note that the two studies shared, in the whole, the preferential expression of 11 genes.…”
Section: Downregulationmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, using quantitative PCR, we previously found that with advancing gestation RhoB expression is significantly increased in human (5) and mouse (unpublished results) ductussimilar to what Dr. Coceani's laboratory observed in fetal rats. However, in sheep (3,4)) and baboon (unpublished results) ductus there was no increase or decrease in RhoB expression. Although we have not examined the expression of calmodulin by quantitative PCR among the different species, it is quite possible that its expression might also vary depending on the species studied.…”
mentioning
confidence: 81%